Studies on the regulation of plasma cholesterol levels in squirrel monkeys of two genotypes - Hugh B. Lofland, Jr.; Thomas B. Clarkson; Richard W. St. Clair; Noel D.M. Lehner (Journal of Lipid Research, 1972)
Certain individual squirrel monkeys (“hyporesponders”) are able to remain normocholesterolemic when fed diets containing cholesterol (0.5 mg/kcal). Other squirrel monkeys (“hyperresponders”) when fed the same diet become hypercholesterolemic. The purpose of these studies was to identify the mechanisms which allow hyporesponders to compensate for dietary cholesterol.Using formula diets and sterol balance techniques, we have compared cholesterol absorption, synthesis, excretion, and turnover in hypo- and hyperresponding monkeys. Cholesterol absorption was essentially identical in the two groups (about 55 mg/day). Cholesterol synthesis was likewise similar in the two groups (about 35 mg/day) and there was no evidence of feedback inhibition at the level of cholesterol fed. Hyporesponders had faster turnover rates and smaller body cholesterol pools than did hyperresponders. Excretion of neutral steroids was similar for hypo- and hyperresponders and did not change with cholesterol feeding. In contrast, hyporesponders increased bile acid excretion shortly after cholesterol feeding was begun. Hyperresponders responded more slowly and to a lesser degree. It is concluded that, in this species, the mechanism of control of plasma cholesterol levels is related to the rate of conversion of cholesterol to bile acids.